Determination the Invert Level of a Stilling Basin to Control Hydraulic Jump - Farzin Salmasi (Global Journal of Food and Agribusiness Management, 2021)
When water is released over the chutes/spillway, the potential energy is converted into kinetic energy at the base of chutes. This energy must be dissipated in order to prevent the possibility of sever scouring of downstream riverbed and the undermining of foundation which may cause failure of spillway and dam. For this purpose energy dissipators must be used which perform the energy reduction by converting the kinetic energy into turbulence and finally into heat. The dissipation of energy can be achieved by means of several methods such as stilling basins. The formation of hydraulic jump in the stilling basin will lead to dissipation of excess energy. In this study we use a simple method to determine stilling basin invert elevation in relation to upstream water elevation, design discharge and downstream water/ tail water elevation. Some solved examples have been provided to exhibit the capabilities of the design procedure.